When the Philippines declared war on the United States Laurel and Proclamation No. 30 - De Viana, Augusto V. (2018)
President Jose P. Laurel stands as the only president of the Philippines to declare a state of war on the greatest power on earth. On 22 September 1944, a day after the massive American bombardment of Manila signaling the return of the Americans to the Philippines, President Laurel issued Proclamation No. 30, declaring that a state of war exists between the Philippines and the United States. Examination of the document and Laurel's action proved that the proclamation had no legal and binding effect. Only the legislature can declare a state of war and such declaration should be ratified by the same body. By the time the Japanese realized this serious legal impediment, it was too late. Laurel had already declared martial law and the National Assembly was disbanded. yet, this declaration did not escape the Americans. General Douglas MacArthur once said if he had his way, he would have Laurel hanged. He also said that Laurel should be thankful to him for not having Laurel tried along with the Prime Minister Hideki Tojo and other Class A war criminals. on the other hand, Laurel said that there was patriotism in collaboration. It depended on how it was given. The collaboration he gave was to save the nation. the collaboration issue was the fault of the United States which failed to grant adequate protection to the Philippines. If General Wainwright did not surrender tot he Japanese, there would be no Executive Commission, no puppet Republic, and therefore, no collaboration.
Keywords: Laurel, Jose Paciano,1891-1959; Philippine-American Post-War -- Relationship